2014
DOI: 10.1007/s11159-014-9436-y
|View full text |Cite
|
Sign up to set email alerts
|

Does private tutoring increase students’ academic performance? Evidence from Turkey

Abstract: This paper investigates the effectiveness of private tutoring in Turkey. The authors introduce their study by providing some background information on the two major national examinations and three different kinds of tutoring. They then describe how they aimed to analyse whether attending private tutoring centres (PTCs) enhances Turkish students' academic performance. By way of multiple linear regression analysis, their study sought to evaluate whether the impact of private tutoring varies in different subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 20 publications
0
36
0
4
Order By: Relevance
“…Unal, Ozkan, Milton, Price and Curva [16], have identified that PT has a strong positive effect on mathematics performance of the all four occupational categories of parents. Another study by Byun and Park [17], has found that students who take commercial SAT preparation courses have positive effect on SAT scores of East Asian American students. Dang [1], have examined the determinants of expenditure on private tutoring and impact of private tuition expenditure on students' performance in Vietnam.…”
Section: Literature On Impact Of Private Tutoringmentioning
confidence: 98%
See 1 more Smart Citation
“…Unal, Ozkan, Milton, Price and Curva [16], have identified that PT has a strong positive effect on mathematics performance of the all four occupational categories of parents. Another study by Byun and Park [17], has found that students who take commercial SAT preparation courses have positive effect on SAT scores of East Asian American students. Dang [1], have examined the determinants of expenditure on private tutoring and impact of private tuition expenditure on students' performance in Vietnam.…”
Section: Literature On Impact Of Private Tutoringmentioning
confidence: 98%
“…Individual level variables related to PT are considered as follows; PT participation (as dummy assigning value 1 if participant), the private tuition expenditure incurred by the household (sum of tuition fee and all other related expenses) [17], number of private tuition classes per week, average private tutoring hours a student take per week. Except the student demography details such as gender, age, socio-economic status of family which comprise of household expenditure, father's and mother's education level and the employment status [1,17,20] were taken as the main controlling factors. Further, this study considered the number of siblings as an explanatory variable [1,2,11,28] because of its spillover effects.…”
Section: Data and Variablesmentioning
confidence: 99%
“…However, empirical findings on the effectiveness of private tutoring are rather contradictory. Among longitudinal studies that controlled for systematic differences between students with and without tutoring, some found a positive effect on achievement (Berberoğlu & Tansel, ; Ireson & Rushforth, ), but others found minimal effects or none at all (Park, Buchmann, Choi, & Merry, ; Ryu & Kang, ; Smyth, ). Therefore, it is not sufficient to ask whether private tutoring per se is effective in improving students’ achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Private tutoring assumes great importance in developing countries. There is a body of literature that analyzes the market for tutoring and estimates effects of private tutoring on various outcomes (Bray and Kwok (2003), Bray et al (2014), Tansel and Bircan (2005), Dang (2007), Gurun and Millimet (2008), Berberoglu and Tansel (2015) etc.). In the context of India, Azam (2016) discusses the incidence of private tutoring over the past several decades.…”
Section: Introductionmentioning
confidence: 99%